Hipoeliticidade global e vetores simultaneamente aproximáveis - Simsen, Jacson (2003)
A necessary and sufficient condition is given for a sum of squares operator to be globally hypoelliptic. This condition is expressed in terms of Diophatine approximation properties of the coefficients. The proof of the Theorem is based on L2− estimates.